Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social